Local Character of Readthrough Activation in Adenovirus Type 5 Early Region 1 Transcription Control - Shen, Li (American Society for Microbiology, 2003)
Wild-type early activity of the adenovirus 5 E1b gene promoter requires readthrough transcription originating from the adjacent upstream E1a gene. This unusual mode of viral transcription activation was identified by genetic manipulation of the mouse β(maj)-globin gene transcription termination sequence (GGT) inserted into the E1a gene. To facilitate further study of the mechanism of readthrough activation, the activities of GGT and a composite termination sequence CT were tested in recombinant adenoviruses containing luciferase reporters driven by the E1b promoter. There was a strict correlation between readthrough and substantial downstream gene expression, indicating that interference with downstream transcription was not a unique property of GGT. Blockage of readthrough transcription of E1a had no apparent effect on early expression of the major late promoter, the next active promoter downstream of E1b. A test for epistatic interaction between termination sequence insertions and E1a enhancer mutations suggested that readthrough activation and E1a enhancer activation of the E1b promoter are mechanistically distinct. In addition, substitution of the human cytomegalovirus major immediate-early promoter for the E1b promoter suppressed the requirement for readthrough. These results suggest that readthrough activation is a “local” effect of a direct interaction between the invading transcription elongation complex and the E1b promoter. DNase I hypersensitivity footprinting provided evidence that this interaction altered an extensive E1b promoter DNA-protein complex that was assembled in the absence of readthrough transcription.